Effect of bariatric surgery on HDL-mediated cholesterol efflux capacity - Castañer, O.; Pérez-Vega, K. A.; Álvarez, S.; Vázquez, S.; Casajoana, A.; Blanchart, G.; Gaixas, S.; Schröder, H.; Zomeño, M. D.; Subirana, I.; Muñoz-Aguayo, D.; Fitó, M.; et al. (Frontiers in Cardiovascular Medicine, 2024)
This original research meets the scope of the research topic "Evidence of atherogenic lipoproteins, what we gain from in vitro and in vivo research." as it focus on the qualitative properties of HDL in patients with obesity treated with bariatric surgery for severe obesity. We performed exvivo invitro cell culture studies to assess the cholesterol efflux capacity and antiinflamatory ability of HDL. We also searched for asociations between the different obesity characteristics with different HDL functions. The effect of a rapid weight loss on the lipid profile and specific qualitative aspects of HDL capacity gives added information on the antiatherogenic mechanisms on patients with obesity affected of low chronic inflammation.